1999
DOI: 10.1073/pnas.96.26.15109
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 and T cell dynamics after interruption of highly active antiretroviral therapy (HAART) in patients with a history of sustained viral suppression

Abstract: Identifying the immunologic and virologic consequences of discontinuing antiretroviral therapy in HIV-infected patients is of major importance in developing long-term treatment strategies for patients with HIV-1 infection. We designed a trial to characterize these parameters after interruption of highly active antiretroviral therapy (HAART) in patients who had maintained prolonged viral suppression on antiretroviral drugs. Eighteen patients with CD4 ؉ T cell counts > 350 cells͞l and viral load below the limits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
538
5
6

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 760 publications
(560 citation statements)
references
References 30 publications
11
538
5
6
Order By: Relevance
“…Despite the long-term suppression of virus replication and the normalization of a series of immunological parameters, which are not limited to the CD4 + T-cell counts but also to the recovery of a series of antigen-specific (including HIV) immunological functions, the interruption of antiviral therapy is almost invariably associated to virus rebound [1,5]. These observations indicated that the long-term suppression of virus replication does not result in the generation of an effective HIV-specific immune response [6].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the long-term suppression of virus replication and the normalization of a series of immunological parameters, which are not limited to the CD4 + T-cell counts but also to the recovery of a series of antigen-specific (including HIV) immunological functions, the interruption of antiviral therapy is almost invariably associated to virus rebound [1,5]. These observations indicated that the long-term suppression of virus replication does not result in the generation of an effective HIV-specific immune response [6].…”
Section: Introductionmentioning
confidence: 99%
“…HIV-1-infected individuals on ART with suppressed plasma viral loads progressively lose HIV-1-specific CTLs, suggesting that persistent viremia is required to maintain high frequencies of HIV-specific CTLs. In chronic HIV-1 infection, discontinuation of ART has been uniformly accompanied by a rapid rebound of plasma HIV-1 RNA to pretreatment, steady-state levels, indicating persistence of the HIV reservoir and absence of immune control (8,20,25). For these reasons, immunotherapeutic strategies with the potential to suppress viral replication and with the goal of eliciting broad, robust, and durable HIV-1-specific TH1 and CTL responses are needed.…”
mentioning
confidence: 99%
“…This and the marked reduction of the infectious load should prolong the lag phase between the interruption of treatment and HIV rebound. Indeed, HIV eclipse times following ARV cessation extended from 1 to 3 days early treatment to 7 days and more during treatment cessation after effective therapy (56)(57)(58). These physiopathological alterations provided the basis for the 7 day treatment on/7 day treatment off trial launched by Dybul et al (13).…”
Section: Treatment Outcomes Following Viral Escapesmentioning
confidence: 99%